Functional Reconstruction of Forehead and Midface Deficits Using the Endoscopic Technique and Bio-Absorbable Implants. Issue 3 (August 2020) - Johnson, Jared; Hojjat, Houmehr; Chung, Michael T.; Arianpour, Khashayar; Rayess, Hani; Eckert, Robert; Carron, Michael
Objectives: Functional deficits of the forehead and midface can pose significant problems for patients varying from mild asymmetry to various degrees of functional impairment including total paralysis. Our objectives were to analyse the use of bio-absorbable implants to reconstruct forehead and midface deficits, all of which were for functional (noncosmetic) reasons. Methods: This study was a retrospective case series between 2008 and 2018. Institutional review board approval was obtained from the Beaumont Health Human Investigation Committee. Surgeries were performed at a tertiary care centre. We evaluated 50 patients who underwent correction of functional deficits of forehead, eyebrow, and midface using the endoscopic technique and bio-absorbable implants. Patient demographics and indicated etiologies and characterization of minor and major complications and their occurrence rates were characterized. Results: Fifty patients were included in the study from 2008 to 2018, with 68% female and 32% male. Combined blepharoplasty and brow lift was the most commonly performed procedure, followed by midface lift and browplasty. The mean follow-up time was 372 days. No major operative complications including stroke, permanent nerve paralysis, or mortality occurred. There was a 4% rate of temporary nerve paresthesia that resolved, 2% rate of infection, and 6% rate of implant migration requiring revision surgery. Conclusion: The endoscopic approach and use of bio-absorbable implants to reconstruct functional deficits of the forehead and midface are safe and effective. There were zero major complications and most of the minor complications were temporary. There was a significant association between non-age-related functional impairment and risk of complication.